The Chinese writing system in Asia an interdisciplinary perspective - Li, Yu 1978- (Routledge, Taylor & Francis Group, 2020)
"The Chinese Writing System in Asia: An Interdisciplinary Perspective integrates a diverse range of disciplinary approaches in examining how the Chinese script represents and actively shapes personal and social identities in and beyond Asia. It is an ideal read for students and scholars interested in a broad and culturally rich introduction to research on the Chinese writing system. It can also serve as the main text of an undergraduate course on the subject. Key features of this volume include: Insights from studies of the Chinese writing system in linguistics, script reform and technology, gender, identity, literature, and the visual arts; Examples embedded in inquiries of the cultural history and contemporary society of Asia; Rigorous yet accessible discussions of complex concepts and phenomena that assume no prior knowledge of Asian languages or linguistics; Supplementary multimedia materials and resources, including instructional support, available online"--
Keywords: Geschichte; Chinesische Schrift; Asien; Chinese characters / Asia; Chinese characters; Asia